Eplerenone Attenuates Fibrosis in the Contralateral Kidney of UUO Rats by Preventing Macrophage-to-Myofibroblast Transition - Xiong, Yunzhao; Chang, Yi; Hao, Juan; Zhang, Cuijuan; Yang, Fan; Wang, Zheng; Liu, Yunmeng; Wang, Xiangting; Mu, Shengyu; Xu, Qingyou (Frontiers in Pharmacology, 2021)
Severe renal fibrosis often occurs in obstructive kidney disease, not only in the obstructed kidney but also in the contralateral kidney, causing renal dysfunction. Although the mechanisms of injury in obstructed kidney have been studied for years, the pathogenesis of fibrosis in the contralateral kidney remains largely unknown. Here, we examined long-term unilateral ureteral obstruction (UUO) model in male Sprague-Dawley rats and found that macrophage-to-myofibroblast transition (MMT) is contributing to renal fibrosis in the contralateral kidney of UUO rats. Interestingly, this process was attenuated by treatment of eplerenone, a specific blocker of the mineralocorticoid receptor (MR). In-vitro, stimulating MR in primary cultured or cell line macrophages enhances MMT, which were also inhibited by MR blockade. Collectively, these findings provide a plausible mechanism for UUO-induced injury in the contralateral kidney, suggesting the benefit of using MR blockage as a part of treatment to UUO to protect the contralateral kidney thereby preserve renal function.